The Aplikasi Pencarian Tempat Indekos dengan Metode Rekomendasi Social Trust Path - Arthur William; Rendy Christian; Riyandi Riyandi; Putra Edi Mujahid (Journal of Information System Research (JOSH), 2021)
Boarding house is a service that offers a room or a place to live in with a certain amount of payment for a certain period (generally payments per month). Currently, most boarding houses available in Medan still use a manual system to manually record transactions between homestay residents and boarding owners. The application of this manual system often faces various problems, such as the absence of a notification system regarding payment due dates to residents, the difficulty of making complaints to owners and residents cannot find out whether their complaints have been known and responded to by the owner or not, boarding owners must check their records to find out residents which ones have not paid off, so it often takes a long time to obtain the information. To further support the performance of this marketplace, a recommendation feature will be added to the marketplace application. The method that can be used is the Social Trust Path method. The Social Trust Path method is a method of calculating the value of the confidence level of something depending on the level of trust of the user who gives the statement. The tools used to perform analysis and design are use case diagrams. This website is built using PHP coding and MySQL database. The result of this research is a web-based boarding house recommendation application that can be used to provide boarding place information for users.